Analysing Malaysian exports, capital, exchange rate, and income growth through the balance of payments constrained growth model - Ramasamy, Kanageswary; Said, Rusmawati; Ismail, Normaz Wana (Asian Economic and Social Society, 2024)
This research examines Malaysian exports, capital, exchange rate, and income growth through the balance of payments constrained growth model. Malaysia's economy has grown slower in the last several years, as seen by the country's dropping goods exports, weaker ringgit, and decreased influx of foreign capital. This study examines potential economic constraints on Malaysia using the extended Balance of Payments Constrained Growth (BPCG) model, which calculates GDP growth by adding exports, foreign capital positions (FDI and FPI), and exchange rates using quarterly data from 2011 to 2022. The Autoregressive Distributed Lag (ARDL) method is used to estimate the model, and Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) are used to assess the model's robustness. The BPCG model places Malaysia's growth rate at 7.3%, which is higher than the country's actual growth rate of 4.6% for the research period. Policymakers should accelerate the New Industrial Master Plan and National Investment Master Plan 2030 to optimise this potential. These efforts aim to boost economic growth by sustaining foreign capital inflows and exports. Through comprehensive trade agreements, authorities should boost exports, market access, and global economic development. © 2024 AESS Publications. All Rights Reserved.